Leadership cycles, styles, and antecedent factors: the perspective of coaches and young soccer athletes from national Slovak leagues - Lisá, Elena; Sousa, Jacinta; Morais, Catarina; Gomes, António Rui (Frontiers in Psychology, 2023)
Building positive relationships and interactions between coaches and athletes is critical to an athlete's success. The current study aimed to overview how coaches and their young athletes perceive three elements of the Leadership Efficacy Model (philosophy, practice, and criteria). The aim was examined with four goals of analysis: the perceptions of coaches and athletes about coaches' leadership philosophy, practice, and criteria (1); the differences between athletes' and coaches' perceptions of leadership cycles (2); the differences between athletes' and coaches' perceptions of leadership styles (3); and the differences between athletes' and coaches' perceptions of leadership antecedent factors (4). The study involved 304 athletes and 20 coaches competing in the youth national leagues U15, U16, U17 and U19. Two-source data collection was applied: coaches completed the questionnaires from their point of view, and so did athletes. The coaches were paired then with their athletes to compare the answers. Coaches fulfilled Leadership Cycles Questionnaire (LEQ), Multidimensional Scale of Leadership in Sport (MSLS), and Leadership Antecedent Factors Questionnaire (LAFQ). Athletes completed the same questionnaires as the coaches did and also fulfilled the Sport Performance Perception Questionnaire (SPPQ). Athletes' age and SPPQ served as control variables. Both athletes (37.5%) and coaches (40%) perceived that the philosophy of the leadership efficacy model should be increased. Coaches evaluated their philosophy (F = 4.43; p =.036; η 2 = 0.014), support in MSLS (F = 5.05; p =.025; η 2 = 0.016) and active management in MSLS (F = 4.08; p =.044; η 2 = 0.013) higher than their athletes. The athletes assessed the maturity of the team members (LAFQ dimension) (F = 13.98; p ˂.001; η 2 = 0.044), negative feedback in MSLS (F = 6.02; p =.015; η 2 = 0.020) and passive management in MSLS (F = 4.95; p =.027; η 2 = 0.016) higher than their coaches. The tendency of coaches to have a more positive perception of their leadership behavior compared to their athletes represents the coach-athlete perception gap of